Bioimaging using bipolar electrochemical microscopy with improved spatial resolution. Issue 21 (21st August 2020) - Iwama, Tomoki; Inoue, Kumi Y.; Abe, Hiroya; Matsue, Tomokazu; Shiku, Hitoshi
Abstract : In this study, we developed bipolar electrochemical microscopy (BEM) using a closed bipolar electrode (cBPE) array with an electrochemiluminescence (ECL) detecting system. Abstract : In this study, we developed bipolar electrochemical microscopy (BEM) using a closed bipolar electrode (cBPE) array with an electrochemiluminescence (ECL) detecting system. Because cBPEs are not directly connected to a detector, high spatio-temporal resolution imaging can be achieved by fabricating a microelectrode array in which each electrode point is arranged in a short interval. A cBPE array with individual cBPEs arranged in 41 μm intervals was successfully fabricated by depositing gold in the pores of a track-etched membrane using electroless plating. Using BEM with the cBPE array, which has a higher density of electrode points than the conventional multi-electrode array, we effectively demonstrated the imaging of [Fe(CN)6 ] 3− diffusion and the respiratory activity of MCF-7 spheroids with high spatio-temporal resolution.